Market Day as a Vehicle for Regional Cultural and Culinary Education for Early Childhood Education - Puput Nurhayati; Erni Munastiwi; Raden Rachmy Diana (Institut Agama Islam Negeri Madura, 2025)
Market day activity is an activity adopted by schools to promote culture and regional food in Indonesia to children, the reality today we often encounter is that early childhood children prefer fast food to traditional food, because the food is increasingly scarce in their environment. Then there are still many parents who think that traditional food is ancient and outdated food, when in fact the food is healthier than the quality of the ingredients used or the way it is made. In this study, the author analyzes and describes how the introduction of regional food through market day activities in RA. Labschool IIQ Jakarta and what are the shortcomings and advantages of these activities. This study uses a descriptive qualitative approach with three data collection techniques, namely: observation, ducumentation and interview. The interviews conducted in this study were through open-ended questions using video converence, zoom meetings with teachers and several guardians, and direct meetings with the Head of RA. Labschool IIQ Jakarta. This research was carried out in November-December 2023 at RA. Labschool IIQ Jakarta. The results of this study show that market day activities are very effective in being carried out by schools to educate students in the introduction of regional food. The advantages felt after the introduction of regional food through market day activities in RA. Labschool IIQ Jakarta is that children can know and experience various kinds of food from different cultural tribes through fun activities, children can also learn about simple mathematical concepts, entrepreneurial skills, and the ability to socialize well.